IFALD in children: What's new? A narrative review - Di Dato, Fabiola; Iorio, Raffaele; Spagnuolo, Maria Immacolata (Frontiers in Nutrition, 2022)
Intestinal failure-associated liver disease (IFALD) is a progressive liver disease complicating intestinal failure (IF). It is a preventable and reversible condition, but at the same time, a potential cause of liver cirrhosis and an indication to combined or non-combined liver and small bowel transplantation. The diagnostic criteria are not yet standardized, so that its prevalence varies widely in the literature. Pathophysiology seems to be multifactorial, related to different aspects of intestinal failure and not only to the long-term parenteral nutrition treatment. The survival rates of children with IF have increased, so that the main problems today are preventing complications and ensuring a good quality of life. IFALD is one of the most important factors that limit long-term survival of patients with IF. For this reason, more and more interest is developing around it and the number of published articles is increasing rapidly. The purpose of this narrative review was to focus on the main aspects of the etiology, pathophysiology, management, prevention, and treatment of IFALD, based on what has been published mainly in the last 10 years. Controversies and current research gaps will be highlighted with the aim to pave the way for new project and high-quality clinical trials.